The promise of transformed long-term care homes: Evidence from the pandemic. Issue 1 (January 2022) - Power, G. Allen; Carson, Jennifer
A combination of factors during the SARS-CoV-2 pandemic led to a disproportionately high mortality rate among residents of long-term care homes in Canada and around the globe. Retrospectively, some of these factors could have been avoided or minimized. Many infection control approaches recommended by public health experts and regulators, while well intended to keep people safe from disease exposure, threatened other vital aspects of health and well-being. Furthermore, focusing narrowly on infection control practices does not address long-standing operational and infrastructural factors that contributed significantly to the pandemic toll. In this article, we review traditional (ie. institutional) long-term care practices that were associated with increased risk during the pandemic and highlight one transformational model (the Green House Project) that worked well to protect the lives and livelihood of people within congregate care settings. Drawing on this evidence, we identify specific strategies for necessary and overdue improvements in long-term care homes.